1963
DOI: 10.1152/ajplegacy.1963.204.5.847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histamine on adrenal 17-hydroxycorticoid secretion in unanesthetized dogs

Abstract: Dogs with previously sectioned dorsal spinal roots (T11-L3) were used in experiments for collecting the adrenal venous blood without anesthetizing or evoking any pain. Intravenous injection of histamine in doses of 0.05–1.0 mg/kg body wt. was demonstrated to produce a marked acceleration of 17-hydroxycorticoid secretion. The time courses of changes in the secretion rate after injection of varying doses of histamine are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1964
1964
1985
1985

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Adrenal cortical response to histamine was studied by a number of investiga tors. Adrenal 17-OHCS secretion in response to histamine was directly and quantitatively evaluated in conscious dogs by Suzuki et al (1963) and in anesthe tized dogs by Katsuki et al (1967) and Tanigawa (1967). The increase in adrenal 17-OHCS secretion after injection of histamine was abolished or markedly reduced by hypophysectomy (Tanigawa 1967) or anterior hypothalamic lesions (Katsuki et al 1967).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adrenal cortical response to histamine was studied by a number of investiga tors. Adrenal 17-OHCS secretion in response to histamine was directly and quantitatively evaluated in conscious dogs by Suzuki et al (1963) and in anesthe tized dogs by Katsuki et al (1967) and Tanigawa (1967). The increase in adrenal 17-OHCS secretion after injection of histamine was abolished or markedly reduced by hypophysectomy (Tanigawa 1967) or anterior hypothalamic lesions (Katsuki et al 1967).…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that an administration of histamine results in a marked increase in adrenal cortical (Suzuki et al 1963, Katsuki et al 1967, Tanigawa 1967 as well as adrenal medullary (Wada et al 1940 Since the differential response of the adrenal cortex and medulla to bacterial endotoxin (Egdahl 1959), cyanide anoxia (Suzuki et al 1965) and muscular exercise (Ohukuzi 1966, Suzuki et al 1967) has already been demonstrated, it is of interest to contrast the adrenal medullary and cortical responses to histamine.…”
mentioning
confidence: 99%
“…The adrenal venous blood was collected without anesthesia by a slight modification of the method of Satake et al (1927), as was done in our previous studies (Suzuki et al 1959(Suzuki et al , 1963(Suzuki et al , 1967. In order to collect the adrenal venous blood samples from conscious dogs without provoking any pain, the dorsal spinal roots of T11-L3 were cut under sodium pentobarbital (25 mg/kg, i.v.)…”
Section: Methodsmentioning
confidence: 99%
“…The adrenal venous blood collection was performed by using a modification of the method of Satake, Sugawara and Watanabe,2 as was done in our previous stu dies. 1,[3][4][5][6][7] The dorsal spinal roots of the 11th thoracic to the 3rd lumbar spinal cord segments, in which the sensory nerve fibers from the lumbar region run, were cut under sodium pentobarbital (25 mg/kg, i.v.) anesthesia.…”
Section: Methodsmentioning
confidence: 99%